Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2568225.2568260
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of the pull-based software development model

Abstract: The advent of distributed version control systems has led to the development of a new paradigm for distributed software development; instead of pushing changes to a central repository, developers pull them from other repositories and merge them locally. Various code hosting sites, notably Github, have tapped on the opportunity to facilitate pull-based development by offering workflow support tools, such as code reviewing systems and integrated issue trackers. In this work, we explore how pull-based software de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
521
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 507 publications
(536 citation statements)
references
References 30 publications
12
521
0
3
Order By: Relevance
“…GitHub has tapped into the opportunity to facilitate pull-based development by offering workflow support tools, such as code reviewing systems and integrated issue trackers. Gousios et al reported the impacts of pullbased development based on mining repository data: fast development, transparency in project management, attracting contributions, crowd sourcing of code review, and democratizing development [3]. GitHub is also considered as a developers' social networking service, and it promotes software development through formal and informal collaboration, called social coding.…”
Section: Introductionmentioning
confidence: 99%
“…GitHub has tapped into the opportunity to facilitate pull-based development by offering workflow support tools, such as code reviewing systems and integrated issue trackers. Gousios et al reported the impacts of pullbased development based on mining repository data: fast development, transparency in project management, attracting contributions, crowd sourcing of code review, and democratizing development [3]. GitHub is also considered as a developers' social networking service, and it promotes software development through formal and informal collaboration, called social coding.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, GitHub also provides various software project development data. Hence, the data of GitHub has been widely used in previous studies [26][27][28][29][30].…”
Section: Subject Projectsmentioning
confidence: 99%
“…Previous studies have also excluded a number of OSS projects after their initial sampling. Samoladas et al (2010) and Gousios and Pinzger (2014) applied certain selection criteria to exclude projects from their initial selection. Midha and Palvia (2012) based on certain project selection criteria, reduced their initial sample from 887 to 283.…”
Section: Storage Of Projects Metadata and Revisionsmentioning
confidence: 99%